The stellar mass density at z approximate to 6 from Spitzer imaging of i '-drop galaxies - Eyles, L; Bunker, A; Ellis, R; Lacy, M; Stanway, E; Stark, D; Chiu, K (2007)
We measure the ages, stellar masses, and star formation histories of z ∼ 6 galaxies, observed within 1 Gyr of the big bang. We use imaging from the Hubble Space Telescope (HST) and the Spitzer Space Telescope from the public 'Great Observatories Origins Deep Survey' (GOODS), coupled with ground-based near-infrared imaging, to measure their spectral energy distributions (SEDs) from 0.8-5 μm, spanning the rest-frame ultraviolet (UV) and optical. From our sample of ≈50 'i′'-drop' Lyman-break star-forming galaxies in GOODS-South with z′AB < 27, we focus on ≈30 with reliable photometric or spectroscopic redshifts. Half of these are confused with foreground sources at Spitzer resolution, but from the 16 with clean photometry we find that a surprisingly large fraction (40 per cent) have evidence for substantial Balmer/4000-Å spectral breaks. This indicates the presence of old underlying stellar populations that dominate the stellar masses. For these objects, we find ages of ∼200-700 Myr, implying formation redshifts of 7 ≤ zf ≤ 18, and large stellar masses in the range ∼1-3 × 1010M⊙. Analysis of seven i′-drops that are undetected at 3.6 μm indicates that these are younger, considerably less massive systems. We calculate that emission line contamination should not severely affect our photometry or derived results. Using SED fits out to 8 μm, we find little evidence for substantial intrinsic dust reddening in our sources. We use our individual galaxy results to obtain an estimate of the global stellar mass density at z ∼ 6. Correcting for incompleteness in our sample, we find the z ∼ 6 comoving stellar mass density to be 2.5 × 106 M⊙ Mpc-3. This is a lower limit, as post-starburst and dust-obscured objects, and also galaxies below our selection thresholds, are not accounted for. From our results, we are able to explore the star formation histories of our selected galaxies, and we suggest that the past global star formation rate may have been much higher than that observed at the z ∼ 6 epoch. The associated UV flux we infer at z > 7 could have played a major role in reionizing the Universe. © 2006 RAS.